Comparative Analysis of Performance Between Sharia Commercial Banks and Sharia Business Units Using the Eagles Method for The 2021-2023 Period - Safitriyanti Safitriyanti; Wiralestari Wiralestari; Rico Wijaya Z (Green Publisher Indonesia, 2025)
This research aims to see how the performance compares between Sharia Commercial Banks and Sharia Business Units using the EAGLES method in the 2021-2023 period. The population of this research is all Sharia Commercial Banks and Sharia Business Units registered with the financial services authority, totaling 38 banks. Using purposive sampling, the sample in this research is 31 bank, consisting of 12 Sharia Commercial Banks and 19 Sharia Business Units. The method used in this research is quantitative with secondary data obtained from the financial reports of each Sharia Commercial Bank and Sharia Business Unit which have been published on the financial services authority website or through the website of each Bank. The data analysis method used is independent sample t test. The results of this research show that based on the eagles method, there are no significant differences in the ratios of ROA, NPF, LGR, DGR and SRQ by personnel between Sharia Commercial Banks and Sharia Business Units. Meanwhile, the FDR and CAR ratios have significant differences between Sharia Commercial Banks and Sharia Business Units. The results of comparing each ratio between Sharia Commercial Banks and Sharia Business Units, in general, the performance of Sharia Business Units is better than that of Sharia Commercial Banks, seen from the average value of each ratio.